Benign liver lesions 2022: Guideline for clinical practice of Associazione Italiana Studio del Fegato (AISF), Società Italiana di Radiologia Medica e Interventistica (SIRM), Società Italiana di Chirurgia (SIC), Società Italiana di Ultrasonologia in Medicina e Biologia (SIUMB), Associazione Italiana di Chirurgia Epatobilio-Pancreatica (AICEP), Società Italiana Trapianti d'Organo (SITO), Società Italiana di Anatomia Patologica e Citologia Diagnostica (SIAPEC-IAP) – Part II - Solid lesions. Issue 12 (December 2022) - Pompili, Maurizio; Ardito, Francesco; Brunetti, Enrico; Cabibbo, Giuseppe; Calliada, Fabrizio; Cillo, Umberto; de Sio, Ilario; Golfieri, Rita; Grova, Mauro; Gruttadauria, Salvatore; Guido, Maria; Iavarone, Massimo; et al.
Abstract: Benign liver lesions are increasingly diagnosed in daily clinical practice due to the growing use of imaging techniques for the study of the abdomen in patients who have non-specific symptoms and do not have an increased risk of hepatic malignancy. They include simple or parasitic hepatic cysts and solid benign tumors which differ widely in terms of prevalence, clinical relevance, symptoms and natural history and often lead to significant clinical problems relating to diagnosis and clinical management. Following the need to have updated guidelines on the management of benign focal liver lesions, the Scientific Societies mainly involved in their management have promoted the drafting of a new dedicated document. This document was drawn up according to the present Italian rules and methodologies necessary to produce clinical, diagnostic, and therapeutic guidelines based on evidence. Here we present the second part of the guideline, concerning the diagnosis and clinical management of hemangioma, focal nodular hyperplasia, and hepatocellular adenoma.